2019
DOI: 10.1371/journal.pone.0225829
|View full text |Cite
|
Sign up to set email alerts
|

Global longitudinal strain can predict heart failure exacerbation in stable outpatients with ischemic left ventricular systolic dysfunction

Abstract: BackgroundDespite advancements in pharmacological and device-based treatment, heart failure (HF) continues to impose an enormous burden for health care system worldwide. Decompensation of HF is one of the main causes of hospitalization, therefore the identification of patients with the highest risk of such complication is still of great clinical importance. The prognostic significance and utility of global longitudinal strain (GLS) has been previously studied in patients with the broad spectrum of cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Our data demonstrate the clinical utility of RV-FWS and RA-GS as echocardiographic parameters that aid in this task. Strain parameters have been previously used to predict outcomes in congestive heart failure and myocardial infarction with similar results ( 21 , 22 ), as well as in PH ( 23 – 25 ). The echocardiographic estimation of sPAP and accordingly the development of the probability of PH is usually predicated on the presence of a complete tricuspid regurgitation envelope by continuous-wave Doppler.…”
Section: Discussionmentioning
confidence: 96%
“…Our data demonstrate the clinical utility of RV-FWS and RA-GS as echocardiographic parameters that aid in this task. Strain parameters have been previously used to predict outcomes in congestive heart failure and myocardial infarction with similar results ( 21 , 22 ), as well as in PH ( 23 – 25 ). The echocardiographic estimation of sPAP and accordingly the development of the probability of PH is usually predicated on the presence of a complete tricuspid regurgitation envelope by continuous-wave Doppler.…”
Section: Discussionmentioning
confidence: 96%
“…Herewith, this study confirms and increases previous evidence on the added prognostic value of GLS over LVEF. Several studies have shown that “baseline” GLS carries prognostic value over LVEF ( 1 , 3 , 5 , 7 ). A meta-analysis by Kamal et al ( 3 ) showed that baseline GLS was more strongly associated with mortality than LVEF.…”
Section: Discussionmentioning
confidence: 99%
“…Global longitudinal strain (GLS) is independently associated with all-cause mortality, cardiovascular death and heart transplantation ( 2 , 5 , 6 ), and also predicts risk of HF hospitalization ( 4 , 7 ). When compared to LVEF, GLS has incremental prognostic value ( 3 , 8 , 9 ) and carries potential to be used as a standard measurement for chronic HF ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…1,10,30 Several relevant risk factors for poorer HF prognosis have been reported and those were confirmed in our study. 13,[31][32][33][34][35][36][37][38][39] The MADIT II (Multicenter Automatic Defibrillator Implan tation Trial II) cohort analysis identified re nal failure as one of the strongest predictors of poor prognosis. 35 Gheorghiade et al 36 and Ambrosy et al 37 listed renal failure and low systolic blood pressure among factors influ encing the prognosis of patients hospitalized for HF.…”
Section: Supplementary Materialsmentioning
confidence: 99%